1995
DOI: 10.1038/jcbfm.1995.105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acetylcholinesterase Modulates the Autoregulation of Cerebral Blood Flow and Attenuates Ischemic Brain Metabolism in Hypertensive Rats

Abstract: Summary:We designed the present study to examine whether or not the inhibition of acetylcholinesterase mod ulates cerebral microcirculation in hypotension and im proves brain metabolism in ischemia induced by bilateral carotid artery occlusion in hypertensive rats. Blood flow to the parietal cortex was determined by the H2 clearance method. Lactate, pyruvate, and ATP were estimated by enzymatic methods. Acetylcholinesterase inhibitor (AChEI, ENA-713), at 0.05, 0.1, or 0.5 mg/kg, was intra venously injected lO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…In animal models, ChE-Is induce vascular relaxation and improve CBF in the ischaemic brain (Sadoshima et al, 1995 ;Tanaka et al, 1994Tanaka et al, , 1995Tsujimoto et al, 1993). Furthermore, treatment with ChE-Is may prevent cholinergic deficits and reduce pyramidal cell loss in ischaemic hippocampus (Tanaka et al, 1994(Tanaka et al, , 1995.…”
Section: Cholinergic Neurotransmission and Rcbfmentioning
confidence: 98%
“…In animal models, ChE-Is induce vascular relaxation and improve CBF in the ischaemic brain (Sadoshima et al, 1995 ;Tanaka et al, 1994Tanaka et al, , 1995Tsujimoto et al, 1993). Furthermore, treatment with ChE-Is may prevent cholinergic deficits and reduce pyramidal cell loss in ischaemic hippocampus (Tanaka et al, 1994(Tanaka et al, , 1995.…”
Section: Cholinergic Neurotransmission and Rcbfmentioning
confidence: 98%
“…Animal models suggest that sustained cholinesterase inhibition may have a role in the treatment of ischemiainduced neurodegenerative disease [56][57][58][59]. Treatment with rivastigmine mitigated cholinergic deficits, reduced pyramidal loss, and attenuated the increase in activated glia in the ischemic hippocampus [56,57].…”
Section: Subcortical Ischemia and Cerebrovascular Lesionsmentioning
confidence: 99%
“…Another possible explanation for the increase in effect on cognition in patients with AD observed with rivastigmine therapy may be the ability of the agent to increase cerebral blood flow. [25][26][27] It has been suggested that decreased cerebral blood flow may precede and or contribute to neuronal degeneration in AD.…”
Section: Commentmentioning
confidence: 99%